Nanocarrier-based delivery of siRNA therapeutics in rheumatoid arthritis: immune mechanisms and translational perspectives - Bai, Longbin; Su, Peng (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent synovial inflammation, pannus formation, and progressive joint destruction. Conventional therapies, including methotrexate, NSAIDs, and biologics, have improved outcomes but remain limited by incomplete efficacy, adverse effects, and resistance. Small interfering RNA (siRNA) has emerged as a promising strategy due to its ability to selectively silence pathogenic genes such as TNF-α, IL-1β, IL-6, IL-17, VEGFA, and key signaling pathways including NF-κB, JAK/STAT, and MAPK. Preclinical studies have shown that siRNA can suppress inflammation, reduce pannus formation, and protect cartilage; however, clinical translation is hindered by instability, nuclease degradation, poor biodistribution, and off-target effects. Nanocarrier-based systems offer solutions by improving siRNA stability, cellular uptake, and targeted delivery to inflamed joints. Lipid nanoparticles, PLGA, chitosan, and polyethyleneimine have been widely studied, while emerging carriers such as dendrimers, self-assembling peptides, mesoporous silica, and metal-organic frameworks (MOFs) further enhance controlled release and specificity. Functional modifications with ligands such as folic acid, hyaluronic acid, or RGD peptides enable active targeting, and stimuli-responsive designs allow pH-, ROS-, or enzyme-triggered release. Theranostic platforms also provide opportunities for real-time monitoring of biodistribution and therapeutic efficacy. Overall, siRNA-based nanomedicine represents a promising therapeutic paradigm for rheumatoid arthritis; however, its clinical translation remains constrained by several important challenges. Although current nanocarrier platforms demonstrate strong gene-silencing efficiency and encouraging anti-inflammatory outcomes in preclinical models, their behavior in humans is far less predictable. Key obstacles—including systemic stability, protein corona formation, endosomal escape efficiency, batch-to-batch manufacturing consistency, and long-term biosafety—must be rigorously addressed before clinical application can be realized. In addition, the heterogeneous nature of RA and its fluctuating inflammatory microenvironment imply that a single siRNA target or delivery strategy may not be universally effective across patient populations. Regulatory considerations also pose significant barriers, as siRNA nanomedicines must meet strict requirements for GMP production, quality control, sterility, pharmacokinetics, immunogenicity, and degradation profiling.